Natural Polarization and Electrooptics Comparison for Evaluation of Cooking Oil Total Quality - Sugito, Heri; Firdausi, Ketut Sofjan (JURNAL SAINS DAN MATEMATIKA, 2014)
In this study, the phenomena of natural polarization and electrooptics effect have been compared as alternative methods for evaluation of vegetable oil quality. The sample used in the experiment was various vegetable oils. The change of light polarization was measured using a pair of polarizer for natural polarization and in case of electrooptics with addition of induced external electric field through DC high voltage. The result has shown that both methods are able to indicate the level of various oil quality. The natural polarization is very useful for preliminary test of oil quality. In the other hand, the electrooptics has a good prospect as single physical indicator for vegetable oil quality.